NATO Science Series II: Mathematics, Physics and Chemistry
DOI: 10.1007/1-4020-3475-x_11
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Donors in Zinc Oxide

Abstract: Abstract:Zinc oxide (ZnO) has emerged as a leading material for micro-and optoelectronic applications. Although the fabrication of ZnO, from nanocrystals to bulk single crystals, is well established, a major roadblock for fabricating optoelectronic devices is the lack of reliable p-type doping. The presence of compensating donors inhibits the growth of p-type ZnO. In this paper, studies pertaining to the microscopic structure and doping properties of hydrogen in ZnO are described. Results from infrared (IR) sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The 'shallow-donor behavior' of H in ZnO has been predicted from theoretical calculations [7,8] and confirmed experimentally [12,13,18,[32][33][34][35][36]. As we have already mentioned in the introduction section, these donors are mainly hydrogen interstitials (Hi) formed either in a Zn-O bond-centered configuration (H BC ) [12,34,35] or as an O-H complex in anti-bonding configuration perpendicular to the c-axis (H AB ) [13,18,36]. Furthermore, there are both theoretical and experimental studies for the existence of hydrogen forming multicenter bonds with oxygen vacancy (V O ), known as H O [14,34], acting as a shallow donor too.…”
Section: Optical and Electrical Properties Of Zno Filmsmentioning
confidence: 62%
See 1 more Smart Citation
“…The 'shallow-donor behavior' of H in ZnO has been predicted from theoretical calculations [7,8] and confirmed experimentally [12,13,18,[32][33][34][35][36]. As we have already mentioned in the introduction section, these donors are mainly hydrogen interstitials (Hi) formed either in a Zn-O bond-centered configuration (H BC ) [12,34,35] or as an O-H complex in anti-bonding configuration perpendicular to the c-axis (H AB ) [13,18,36]. Furthermore, there are both theoretical and experimental studies for the existence of hydrogen forming multicenter bonds with oxygen vacancy (V O ), known as H O [14,34], acting as a shallow donor too.…”
Section: Optical and Electrical Properties Of Zno Filmsmentioning
confidence: 62%
“…In addition, hydrogen could form multicenter bonds at oxygen vacancy (V O ) sites (H O ). In the case of polycrystalline ZnO thin films, Kim et al [17] observed that H causes passivation of grain boundaries and suggested that the main source of n-type carriers was H i s and that H O s were much less than H i s. It has also been found that H AB s are rather unstable and their number declines with time, perhaps due to the formation of hydrogen molecules (H 2 ) [18]. According to Huang et al [11] H improves conductivity and crystallinity, as it causes larger faceted grains, which, in turn, is attributed to both surface fast diffusion and etching.…”
Section: Introductionmentioning
confidence: 99%
“…Later, post growth doping of ZnO has been reported by several others [19], [11] and for both ZnO and MgZnO [7]. In these studies, the effect of doping was found to necessitate annealing the ZnO samples at temperatures of at least 300 ˚C and up to 700-800 ˚C.…”
Section: Discussionmentioning
confidence: 94%
“…The literature research conducted [22][23][24][25][26], allowed us to formulate the following considerations. The kinetics expression of CuO reduction reaction and its parameters are available in literature, it has been possible to verify the time needed to reach a 0.9 conversion:…”
Section: Discussion On Kineticsmentioning
confidence: 99%